Action and Advocacy for Sustainable Transport : Recent and Ongoing World Bank Efforts - Guislain, Pierre; Irigoyen, Jose Luis (World Bank, Washington, DC, 2016)
During its 2014–15 fiscal year, the World Bank’s transport strategy focused on sustainability as part of a broader effort to eradicate poverty, raise shared prosperity, and tackle climate change. As articulated by the UN Secretary General’s High-Level Advisory Group on Sustainable Transport, sustainability encompasses heightened access in rural and landlocked areas, low-carbon solutions in cities, and world trade and growth stimulated by investments in infrastructure, inter-modality, and digital and low-carbon technologies. The World Bank’s new commitments in fiscal year 2015 reflected this convergence, and its operational focus has been backed by strong advocacy on transport issues in recent global conferences and high-level summits.